Plasminogen Activator Inhibitor 1 and Plasminogen Activator Inhibitor 2 in Various Disease States - Kruithof, Egbert K O; Gudinchet, Annelise; Bachmann, Fedor (Thrombosis and Haemostasis, 1988)
The association of increased PA-inhibitor (PAI) activity and of PAI-1 and PAI-2 antigen levels with different pathological conditions was studied in a collective of over 300 patients. PAI-1 and PAI-2 levels were measured by specific radioimmunoassays. A good correlation was observed of PAI activity with PAI-1 antigen (r = 0.718; p <0.0001) but not with PAI-2 (r = 0.070; n.s.). Both in the controls and in the patients, PAI activity and PAI-1 antigen showed an extremely large range of values. PAI activity ranged from 0.5 to 68 U/ml and PAI-1 antigen from 6 to 600 ng/ml. Increased PAI activity and PAI-1 antigen was observed in patients with malignant tumors, cardiovascular or thromboembolic disease, in the postoperative phase, with hepatic insufficiency, after trauma and after extracorporeal circulation. The large spectrum of disease states with increased PAI activity and PAI-1 antigen reinforces previous suggestions that PAI-1 is an acute phase reactant. After extracorporeal circulation, PAI activity and PAI-1 concentrations strongly increased within one hour, remained elevated for at least one week and returned to preoperation values within 7 days.PAI-2 values ranged from below detection limit (15 ng/ml), observed in half of the plasmas, to 485 ng/ml in a pregnant woman. High values of PAI-2 were only observed in pregnancy.
Keywords: Tissue-type plasminogen activator; Urokinase; Plasminogen activator inhibition; Plasminogen activator inhibitor type 1 and 2